[Troubled land ; The golden credit card ; Nagalit and bulkan - Lazaro, Cheche (The Probe Team, 1991)
Examines and looks at the Land Reform program of the Aquino government; A case of a lost credit card that continues to be used long after it is reported lost; and a stage play about Mt. Pinatubo's wrath.